Healthcare Use and Non-Recovery in Patients With Spinal Disorders - Kjønø, Lise Grethe; Johnsen, Marianne Bakke; Grotle, Margreth; Hartvigsen, Jan; Clausen, Stine; Wilhelmsen, Maja; Richardsen, Kåre Rønn; Storheim, Kjersti; Magnusson, Karin (European Journal of Pain, 2025)
Background: The association between different patterns of healthcare use and non-recovery in patients with spinal disorders is unclear. We aimed to assess the association between healthcare use and non-recovery 6 months after a specialist evaluation in Norwegian secondary care and whether non-recovery was linked to adherence to specialist-recommended care. Methods: This observational registry-based cohort study includes 3745 patients aged 18–70 years (mean (SD) 46 (12) years, 59% women) from the Norwegian Neck and Back Registry (NNRR). We studied non-recovery 6 months after the specialist evaluation using the Global Perceived Effect (GPE) scale, defined as ‘slightly improved’, ‘unchanged’, ‘slightly worse’, ‘much worse’, or ‘worse than ever’. Using logistic regression, we examined the association between non-recovery and specialist-recommended healthcare (i.e., recommended follow-up in primary or secondary care) and actual healthcare use identified in national registries (visits to general practitioners, physical therapists, and chiropractors in primary care and outpatient and inpatient visits in secondary care). Results: In total, 80% self-reported non-recovery at 6 months. Adherence to specialist-recommended healthcare was not associated with non-recovery (adjusted OR [aOR] 1.09, 95% CI 0.91–1.29). Highest odds for non-recovery were among patients using primary care alone (aOR 1.68, 95% CI 1.37–2.07) or no healthcare (aOR 1.81, 95% CI 1.44–2.27). Secondary care alone (aOR 0.75, 95% CI 0.59–0.96) or combined with primary care (aOR 0.49, 95% CI 0.41–0.59) was associated with recovery. Conclusions: Our findings raise questions about the value of the specialist recommendations and also the content of healthcare services provided after a specialist evaluation. Significance Statement: Our findings suggest that follow-up after specialist evaluation may not adequately meet patient needs, indicating a need for improved management of spinal disorders. Given the low proportion of patients reporting recovery at 6-month follow-up, we highlight the importance of good transitions, care coordination, and coherent messages across sectors and professions. More effective healthcare and reduced sick leave could save societal costs. Moreover, this approach could improve quality of life, enabling a more active and participatory lifestyle.
Publisher Copyright: © 2025 European Pain Federation - EFIC ®.